ناکامی کی حقیقت: سیرت طیبہ ﷺ کی روشنی میں مطالعہ : Failure: A study of Seerat E Tayaaba - Dr. Shaista Jabeen; Dr. Ayesha Tariq (Al Manhal Research Journal, 2023)
Failure is a part of human life. There are no human beings in this world that have never the experience of failure, in fact, most successful persons, fail countless times before they became successful in life. The real thing is to learn from failures and transform them into strength. Failure can be unpleasant and unwanted experience, as no one to fail in any matter by choice, hence it can come in different forms, not achieving the academic grades for students, being unsuccessful in a job application for a career oriented person, a relationship break up for a married person or general set back. While undesirable, failure is also a normal and necessary part of life. Yet, many people will go to significant lengths to avoid failing because the emotions we can feel as a result can be so painful. Nonetheless, a fear of failure can hold us back from taking up the opportunities we might need to succeed. Fear of failure, also known as Atychiphobia is an irrational and persistent fear of failing. This fear can stem from a number of sources. Sometimes it might emerge in response to a specific situation. In other case, it might be related to another mental health condition such as anxiety or depression. As per Islamic perspective failure is something that is not related with worldly failures. Islam connects it with the failure of eternal life, it does not bother the failure of this mortal considering them a test case for its followers so their level of believe upon Allah SWT could be checked. This article will discuss the examples of failures and guidelines to cope with it through prophetic life, so one can understand the exact definition of failure and methodology to overcome it.